Urinary tract complications with rectal surgery. - Beahrs, J R (1978)
The possibility of urinary tract injury should always be considered in the course of anterior resection or combined abdominoperineal resection of the lower colon and rectum. Controlled studies of ureteral and other injuries and fistulas cannot be made; but fortunately, unanticipated damage to the lower urinary tract does not occur often. The surgeon operating in the pelvis should be aware of the problems rarely encountered and should be capable of their management. If a urologic surgeon is available, consultation often is desirable. Prompt intraoperative recognition is most important so remedial procedures can be carried out immediately. Delay in recognition and treatment jeopardizes the patient's course and the function of the urinary tract. Postoperative urinary tract infections should be diagnosed early so prompt treatment can be instituted.